Peluang dan Hambatan Program Keluarga Berencana (KB) Krama Bali di Kelurahan Sesetan (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2023)
This study analyzes the opportunities and barriers to implementing the Balinese family planning program (KB Krama Bali) in Sesetan Village. Balinese family planning program is a family planning program based on Balinese local wisdom that states Balinese people have the right to have more than two children according to the Balinese naming, namely: Wayan, Made, Nyoman, and Ketut with the hope of creating a quality Balinese family. Balinese family planning program has intensified again through Bali Governor Instruction Number 1545 of 2019 with a statement that the names